2020
DOI: 10.1007/s00521-020-05128-7
|View full text |Cite
|
Sign up to set email alerts
|

Hilbert sEMG data scanning for hand gesture recognition based on deep learning

Abstract: Deep learning has transformed the field of data analysis by dramatically improving the state of the art in various classification and prediction tasks, especially in the area of computer vision. In biomedical engineering, a lot of new work is directed toward surface electromyography (sEMG)-based gesture recognition, often addressed as an image classification problem using convolutional neural networks (CNNs). In this paper, we utilize the Hilbert space-filling curve for the generation of image representations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…The experimental results demonstrate that this approach outperforms five baseline machine learning methodologies, indicating the superiority of the recommended strategy. Another study by Tsinganos et al (2021) employs Hilbert space-filling curves to represent sEMG signals in a way that enables the utilization of conventional image processing pipelines such as convolutional neural networks.…”
Section: -Related Workmentioning
confidence: 99%
“…The experimental results demonstrate that this approach outperforms five baseline machine learning methodologies, indicating the superiority of the recommended strategy. Another study by Tsinganos et al (2021) employs Hilbert space-filling curves to represent sEMG signals in a way that enables the utilization of conventional image processing pipelines such as convolutional neural networks.…”
Section: -Related Workmentioning
confidence: 99%
“…In contrast, the convolutional autoencoder (CAE) network [ 30 ] has low dependence on labeled samples for training; that is, CAE networks only need a small number of labeled samples for classification research on the dataset of interest [ 31 , 32 ]. Additionally, despite the lack of practical engineering verification cases concerning the signal dimensional conversion, it has been reported that the encoding operation of a one-dimensional signal based on a pseudo-Hilbert scan can theoretically preserve more of the sample’s original feature [ 33 , 34 , 35 ]. This means that the encoding results of the two-dimensional images are beneficial to the signal feature extraction based on the CAE network.…”
Section: Introductionmentioning
confidence: 99%
“…As SFCs map between d and one dimensions, they are also applicable for Machine Learning (ML) scenarios where data must be mapped into an alternative form appropriate for a given ML model, in some cases with an improvement to the overall accuracy of said model. Instances of this in the literature include the classification of schizophrenia and normal patients' 3D fMRI scans [11], gesture recognition of Surface Electromyography (sEMG) signals represented as images [12], [13], and malware detection and classification using Support Vector Machines [14]. Within the context of low-level computing, the curves have been used in the creation of cache-oblivious loop structures that preserve the locality of data held within the cache [15].…”
Section: Introductionmentioning
confidence: 99%